Active recovery decreases performance during repeated bouts of sprint swimming irrespective of resting interval duration - Toubekis, A.; Tokmakidis, S. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Active recovery (AR) may be a beneficial procedure for cycling performance maintenance during repeated bouts of high intensity exercise as compared to passive recovery (PR) (Bogdanis et al. 1996). However, there are no relevant findings concerning swimming. The purpose of the present study was to examine the effect of AR during a typical sprint swimming training set, performed with short and long duration resting intervals. METHODS Eight male swimmers (mean±SE, body weight: 74±2 kg, age: 21±2 years, height: 178±2 cm) with past competitive experience at national level (currently trained recreationally) performed, on four separate occasions at least six days apart, a set of eight by 25 m repetitions with 120 s or 45 s resting intervals. Recovery between repetitions was either passive (PR120, P45) or active (AR120, AR45). The intensity of AR was set at 60 % of the individual max speed of 100 m. Venous blood sample was taken at rest and during the second minute of recovery after each trial. The tests were performed with a counterbalanced order in a 25 m indoors swimming pool during the same time of the day. The crawl swimming style was used for sprints and AR. All sprints started from push-off and performance times were recorded with an official timing system used during competition. RESULTS Independently of the applied resting interval (e.g.120 s or 45 s), the performance time was decreased when AR was applied (AR120:14.31±0.09 vs. PR120:13.83±0.07s,& AR45:15.11±0.21 vs. PR45:14.55±0.15s, main effect trials & interaction, p<0.05). The recorded time during the first sprint was the same in all four trials. After the first sprint, performance in the PR120 trial was maintained up to the 6th sprint, whereas in the PR45 trial up to the 2nd sprint (p>0.05). During both AR trials, performance was reduced after the first sprint (main effect sprints, p<0.05). Blood lactate was higher after the PR120 as compared to AR120 trial (17.21±0.9 vs. 14.39±0.8 mmol/l, p<0.05). There was no difference in blood lactate concentration after PR45 (17.13±1.4 mmol/l) and AR45 (15.31±1.2 mmol/l) trials. Plasma ammonia after the completion of the 8th sprint was increased compared to resting values (p<0.05) but no difference was observed between trials (PR120:92±9_mol/l, AR120:121±13_mol/l, PR45:121±22_mol/l, AR45:141±23_mol/l, main affect trials, p>0.05). Plasma volume changes after the repeated bouts (PR120: -11.7±1.0 %, AR120: -13.1±1.6 %, PR45: -15.5±1.4 %, AR45: -12.8±1.1%) were no different between trials (p>0.05). DISCUSSION The present findings discourage the use of active recovery at intensity 60% during sprint swimming training sets, because performance will decrease probably due to incomplete restoration of high-energy phosphates. Passive recovery may be preferable. Nevertheless, further research is needed for the evaluation of active recovery on well-trained swimmers.